MITIGASI SOSIAL DI KOTA TERPADU MANDIRI (KTM) LABANGKA SUMBAWA BESAR NTB - Sudaru Murti (Jurnal Penelitian Humaniora, 2012)
Every development program, physical or non physical, aims to increase the welfare of society. The transmigration program's goals also includes the increase of income and improving the quality of life of its participants. Nevertheless, several problems can be found within the execution of the transmigration program, such as the location of transmigration or with the participants themselves. While the environment and society undergoes change, a review of the environmental mitigation must be done in order to achieve maximum results. The synergy of change brings a variety of effects such as the segregation of culture, environmental order and a new rule of order. Therefore, a social mitigation review in the location of transmigration using qualitative – participative method using field observation and in- depth interview, hopes to contribute to the execution of the transmigration program. Findings from the field must be equipped with a variety of infrastructure, especially social technology in order to quickly achieve an increasing speed of social capital. By strengthening institutions and increasing participation, it is hoped that the execution of development in the transmigration sector will quickly achieve maximum results.